Labour induction in postdate pregnancy: when to start – at week 40 or 41 of gestation? - PALIULYTĖ, Virginija; RAMAŠAUSKAITĖ, Diana (Acta medica Lituanica, 2010)
Introduction. Post-term delivery is associated with significantly increased risks of perinatal and maternal complications. The aim of the study was to compare maternal and neonatal complications in two groups: women who delivered at 41 completed weeks (study group) and women who delivered at 40 completed weeks (control group).Materials and methods. This is a retrospective case-control study which included all pregnant women who delivered in the Vilnius City University Hospital (VCUH) from January 1, 2007 to December 31, 2007. Patients were eligible for inclusion in our study if they delivered a live birth beyond 41 weeks of gestation during the study period in the VCUH (n = 182). Using the week of gestation as the primary predictor variable, we examined its association with the following outcomes: mode of delivery, expectant management or labour induction, labour induction method, delivery time, perineal laceration, postpartum hemorrhage, meconium-stained amniotic fluid, oligohydramnios, umbilical artery pH, neonatal morbidity, duration of hospitalisation. From all the women who delivered from 40 completed weeks to 40 weeks + 6 days (n = 193) in the same study period, every tenth woman was selected for the control group.Results. The pregnancy protracts frequently for nulliparous women without reference to mother’s age. Labour induction in them more frequently occurs at 41 completed weeks than in the control group (39.6% vs 14.5%, p < 0.05; OR 0.37), and the main way of induction in prolonged pregnancies is vaginal prostaglandins. The mother and her newborn at 41 completed weeks tend to have a higher risk of oligohydramnios (10.4% vs 5.2%, p < 0.05; OR 0.5), umbilical cord rotation around the baby’s neck (57% vs 43%, p < 0.05; OR 0.7), meconium-stained amniotic fluid (27.4% vs 16.6 %, p < 0.05; OR 0.6), vacuum extraction rate (7.7% vs 3.1%, p < 0.05; OR 0.4), newborn acidosis (45.5 % vs 33.2%, p < 0.05; OR 0.73). When meconium-stained amniotic fluid is diagnosed at 41 completed weeks, the delivery should be monitored more intensively because of a higher risk of newborn acidosis after the labour. The mode of delivery, delivery duration, mother’s injuries, postpartum hemorrhage and complications, also Apgar scores show no significant differences in these groups.Conclusion. When delivery occurs at 41 competed weeks, the results are worse as compared to those of the delivery at 40 completed weeks. Therefore, it is reasonable to induce labour at 40 completed weeks and beyond of gestation. This suggestion requires large prospective studies and a very precise gestation time estimation for all pregnant women before recommending labour induction at 40 competed weeks.Keywords: gestational age, post-term pregnancy, caesarean delivery, labour induction, expectant management, meconium-stained amniotic fluid